Change over time in the type and functions of crib speech around the fourth birthday. (July 2019) - Mead, Danielle L.; Winsler, Adam
Abstract: Crib speech, the monologue speech of a young child before s/he falls asleep, has been examined in very few studies to date. Private speech has been explored in relation to potential motivational and self-regulatory functions, but few studies have examined private speech in pretend play or pre-sleep contexts. This longitudinal case study examines the crib speech of a young girl between the ages of 46 and 50 months by exploring the content of her speech and how it changes over time, relations between types of speech content, and differences between the speech used on days when she did and did not fall asleep. A total of 57, 45-min recordings were collected over four months during her daily nap/quiet time. Utterances were coded as whispered or full volume, spoken or sung/hummed, and social or private. Speech was reliably coded into content categories: self-regulation, fantasy dialogue, emotion content, and language/literacy practice. Growth curve models examined changes in the frequency of different types of speech over time. Crib speech was common, occurring each day, with on average, 340 utterances with 1001 words per day and a mean length of utterance (MLU) of three words. Fantasy role-playing speech and private singing were particularly common, with sung utterances showing more complexity than spoken utterances. MLU followed a non-linear, inverted-U shape curve over time. Language/literacy practice increased over time, while emotional content, fantasy dialogue, and role-playing dialogue followed an inverted U-shape over time. Fewer undecipherable and more emotion-related utterances occurred on days that she fell asleep. Emotion-related speech was positively associated with self-regulatory utterances, and the more she engaged in word play/literacy practice, the less she engaged in fantasy dialogue. Highlights: Crib speech, the monologue speech of a child before s/he falls asleep, has been minimally studied. This case study examines 57 recordings crib speech of a young girl between 46 and 50 months of age. Speech was coded as: self-regulation, fantasy dialogue, emotions, & language/literacy practice. Fantasy role-playing speech and private singing were common. Emotion-related speech was positively associated with self-regulatory utterances.